The Practicality of Interactive Multimedia Based on Scientific Approach in Pascal's Law Material for High School Students - Fitriyana, Fitriyana; Pradananta, Hidayat; Salmah, Ummi; Supriana, Edi (Physics Education Research Journal, 2024)
This study aimed to determine the practicality of interactive multimedia based on a scientific approach to the learning process of Pascal's Law for high school students. This study used a questionnaire instrument consisting of five items, namely (1) media attractiveness and accessibility, (2) media structure and understanding, (3) training and concept mastery, (4) additional aspects, and (5) the impact of using multimedia. The subjects of this study involved physics teachers and 11th-grade MIPA students at Ar Rohmah IIBS Malang High School. The sampling technique in this study was convenience sampling. The data obtained were analyzed using quantitative methods with descriptive analysis techniques. Based on the study results, the percentage of multimedia practicality assessed by teachers reached 85%, while those assessed by students reached 96%. Based on these percentage values, this interactive multimedia based on a scientific approach to the learning process of Pascal's Law for high school students is classified as practical and can be further tested for effectiveness.